GRANICA MIĘDZY JĘZYKIEM MÓWIONYM A STANDARDOWYM - STĘPLEWSKI, ARTUR (Slavia Occidentalis, 2020)
The paper focuses on the relationship between spoken language and standard language. It describes the process of choosing one of the spoken varieties as a basis for a general national language. However, this is a political decision. Linguistics is a secondary tool used in an ideological construct of a nation as an imaginary community. Therefore, any national language is culturally marked. The standard language is used to geographically connect members of a community; it also relates modern users to their ancestors. Politics and linguistics must also rely on the educational system to teach the users one language and to communicate that they are a single nation.